PENGARUH SILICA FUME SEBAGAI BAHAN TAMBAH TERHADAP KARAKTERISTIK BETON MUTU TINGGI - Vincentius Davendra (Jurnal Proyek Teknik Sipil, 2022)
High-strength concrete is concrete with special characteristics that ordinary concrete does not have. High-strength concrete can be defined as concrete with one or more characteristics, such as small shrinkage, low permeability, high elastic modulus, or high compressive strength. Silica Fume (SF) is used as an additive material in concrete mixtures. Silica fume is a waste product of silicon metal or ferrosilicon alloy and have a silica content (SiO2) that is very high at 93.09%. In this research, an analysis of the use of silica fume as a cement additive for high-strength concrete will be carried out with variations in silica fume of 0%, 2.5%, 5%, 7.5%, 10%. With a mixture of added material in the form of a superplasticizer (Consol SS-74) with a percentage of 0.4%. From the results of the research conducted, the highest compressive strength of concrete value is obtained at a percentage of 5% both at the age of 7, 14, and 28 days in a row the value is 43.4 Mpa, 46.3 Mpa, and 55.8 Mpa.